2023
DOI: 10.20944/preprints202301.0445.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Cultivation Modality and Barrier Maturity Modulate the Toxicity of Industrial Zinc Oxide and Titanium Dioxide Nanoparticles on Nasal, Buccal, Bronchial, and Alveolar Mucosa Cell-Derived Barrier Models

Abstract: As common industrial by-products, airborne engineered nanomaterials are considered important environmental toxicants to monitor due to their potential health risks to humans and animals. The main uptake routes of airborne nanoparticles are nasal and/or oral inhalation, which are known to enable the transfer of nanomaterials into the blood stream resulting in rapid distribution in the body. Consequently, mucosal barriers present in nose, buccal and lung have been identified and intensively studied as the key ti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The authors saw no changes in TEER or mitochondrial activity during the 24-hour exposure period. Similarly, Stuetz et al exposed Calu-3 cells to 0.25 mM and 2 mM of TiO2-NPs and ZnO-NPs for 24 hours [65]. They showed that only ZnO-NP exposure caused a decrease in cell viability and TEER at all concentrations.…”
Section: Cultured Human Airway Epithelial (Calu-3) Cellsmentioning
confidence: 99%
“…The authors saw no changes in TEER or mitochondrial activity during the 24-hour exposure period. Similarly, Stuetz et al exposed Calu-3 cells to 0.25 mM and 2 mM of TiO2-NPs and ZnO-NPs for 24 hours [65]. They showed that only ZnO-NP exposure caused a decrease in cell viability and TEER at all concentrations.…”
Section: Cultured Human Airway Epithelial (Calu-3) Cellsmentioning
confidence: 99%